Gravitation - Piersol, Paul Du Chaillu (My University, 1900)
Introduction: The real significance of Newton’s discovery of universal gravitation is fully appreciated by but few. To a certain degree, all men are acquainted with it, for it is the force which gives weight to a body or causes it to fall toward the center of the earth. But it goes still farther, determining the position of the planetary bodies, and holding them in their orbits. A large number of Philosophers before Newton were aware of the motion of terrestrial bodies, and contributed something that aided in the discovery of this law. Of these we will mention but one; Galileo, for it was by looking from the heights of Galileo’s discovery that Newton was enabled to discover the great law which he did. Galileo was born at Pisa, Italy, Feb. 14, 1564. He early showed a fondness for mathematics, and at the age of twenty was a distinguished geometrician. Five years later, he was appointed Professor of Mathematics at Pisa. It was here, while seated in a church that he noticed the slow and uniform swinging of a lamp, and inferred that this principle might be used as a measure of time. This idea he carried out fifty years later. He wrote many excellent treatises on science, and constructed many machines of public utility for the state. Among some of his inventions were the thermometer, the proportional compass, and the microscope. He was the founder of Experimental Science, and first formulated the principle of virtual velocities. He investigated the true laws of motion, and by experiment, demonstrated that gravity acts on all bodies alike, and that bodies of unequal weights will fall through the same space in equal times.
Citation: Piersol, Paul Du Chaillu. Gravitation. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Physics; Gravity; Galileo; Newton; Theses